2023
DOI: 10.1039/d3sm00385j
|View full text |Cite
|
Sign up to set email alerts
|

pH-Tunable electrokinetic movement of droplets

Abstract: Manipulation and control of droplet motion in an electric field is of interest in biological systems, microfluidics and electrokinetic (EK) separation techniques. In this work, we show that the electrokinetic...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 65 publications
(116 reference statements)
0
8
0
Order By: Relevance
“…The frequency of an applied oscillatory electric field is varied up to 10 MHz. The concentration of the background aqueous solution is varied from low to high so that the Debye–Hückel parameter spans up to 100. It may be noted that the magnitude of the surface charge density of various types of fluid droplets including emulsion droplets often ranges up to 10 μC/cm 2 . ,, Besides, the polarity of the surface charge of the droplet may be positive or negative depending on the pH and concentration of the suspended aqueous medium. In our present study, we consider a typical surface charge density within the above-mentioned range in which the Debye–Hückel approximation holds true.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The frequency of an applied oscillatory electric field is varied up to 10 MHz. The concentration of the background aqueous solution is varied from low to high so that the Debye–Hückel parameter spans up to 100. It may be noted that the magnitude of the surface charge density of various types of fluid droplets including emulsion droplets often ranges up to 10 μC/cm 2 . ,, Besides, the polarity of the surface charge of the droplet may be positive or negative depending on the pH and concentration of the suspended aqueous medium. In our present study, we consider a typical surface charge density within the above-mentioned range in which the Debye–Hückel approximation holds true.…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies suggest that various limiting forms of eq are found to be very important for the correct measurement of surface charge, surface potential, and hydrodynamic slip length for perfectly dielectric (under the limit of ϵ d → 0), perfectly conducting (under the limit of ϵ d → ∞) liquid droplets as well as hydrophobic rigid colloids. One of the limiting forms (under the limit of κa ≫ 1) (e.g., Smoluchowski limit) of expression was recently used by Rashidi and Benneker for the correct measurement of the surface potential as well as the surface charge density of dielectric pH-regulated liquid droplets suspended in electrolyte solution at high concentration. Besides, under the limit of ϵ d → ∞, the corresponding limiting form of eq was further used to measure the charge properties of sodium dodecyl sulfate-stabilized decane droplets .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This has potential applications in emulsion destabilization and separations processes. 15 To describe the distribution of electrostatic potential in the EDL, the classic Poisson−Boltzmann (PB) theory assumes that the solvent's relative permittivity remains constant within the EDL. However, various studies have shown that the relative permittivity near a charged surface is lower than its bulk value.…”
Section: ■ Introductionmentioning
confidence: 99%
“…21 It has been indicated that varying permittivity within the EDL formed adjacent to a charged surface impacts the electrostatic potential distribution within the EDL and the effective thickness of the EDL itself. 17,21 Research findings suggest that this phenomenon becomes more prominent when the EDL thickness (λ) is approximately 1 nm and the surface potential of the substrate (ζ-potential) is around ∼10 −1 V. 17 Droplet EP has been thoroughly investigated through theoretical, 22−24 numerical, 25 and experimental 15,26,27 studies and have been reviewed recently. 28 Some studies have considered the effect of variable permittivity within the EDL on EP.…”
Section: ■ Introductionmentioning
confidence: 99%